Building the case for mitochondrial transplantation as an anti-aging cardiovascular therapy - Headley, Colwyn A.; Tsao, Philip S. (Frontiers in Cardiovascular Medicine, 2023)
Mitochondrial dysfunction is a common denominator in both biological aging and cardiovascular disease (CVD) pathology. Understanding the protagonist role of mitochondria in the respective and independent progressions of CVD and biological aging will unravel the synergistic relationship between biological aging and CVD. Moreover, the successful development and implementation of therapies that can simultaneously benefit mitochondria of multiple cell types, will be transformational in curtailing pathologies and mortality in the elderly, including CVD. Several works have compared the status of mitochondria in vascular endothelial cells (ECs) and vascular smooth muscle cells (VSMCs) in CVD dependent context. However, fewer studies have cataloged the aging-associated changes in vascular mitochondria, independent of CVD. This mini review will focus on the present evidence related to mitochondrial dysfunction in vascular aging independent of CVD. Additionally, we discuss the feasibility of restoring mitochondrial function in the aged cardiovascular system through mitochondrial transfer.